Development of TCS3200 Color Sensor Based on Arduino Uno and Its Application in Determining Borax Levels in Food - Khairi Suhud; Sukoma Sukoma; Sitti Saleha; Muhammad Syukri Surbakti (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
A color scanner application using the TCS3200 sensor, Arduino Uno microcomputer with IDE Software Program, a black box container, and a 12x2 matrix display has been designed, built, and tested. This sensor is employed to measure the level of borax in food items such as meatballs, tofu, and noodles in Banda Aceh. The obtained results are then compared with the measurement results of the Standard Ultraviolet-Visible Spectrophotometry (UV-Vis) method. Samples were prepared using centrifuge technique and the filtrate was collected. Subsequently, optical samples were prepared using dried filter paper with curcumin and scanned with the TCS3200 color sensor. Sample collection was carried out at Lamnyong Market, Lamdingin Market, Seutui Market, Suzuya Mall, and Ulee Kareng Market. Sample identification was performed using qualitative analysis, namely the flame test, and quantitative analysis using the TCS3200 color sensor based on Arduino Uno. The results of the quantitative analysis obtained from the TCS3200 color sensor compared with the ultraviolet-visible spectrophotometry (UV-Vis) method as the standard method indicate that the samples of meatballs, tofu, and noodles do not contain the harmful preservative borax. The positive control for borax using the TCS3200 color sensor is 56.8 ppm, while using the UV-Vis spectrophotometer it is 57.6 ppm. The t-test results from both methods show consistency between the TCS3200 color sensor measurement method and UV-Vis spectrophotometer Keywords, Borax, meatballs, tofu, noodles, flame test, TCS3200 color sensor, UV-Vis spectrophotometer